2019
DOI: 10.1002/ptr.6318
|View full text |Cite
|
Sign up to set email alerts
|

miR‐96 and autophagy are involved in the beneficial effect of grape seed proanthocyanidins against high‐fat‐diet‐induced dyslipidemia in mice

Abstract: We aimed to investigate the possible signaling pathways underlying the regulation of grape seed proanthocyanidins extracts (GSPE) on lipid metabolism. One hundred male C57BL/6 mice were divided into four groups: control group (normal diet), GSPE group (normal diet + GSPE), high-fat diet group (HFD), and high-fat diet plus GSPE (200 mg/ kg/day) group (HFD + GSPE). Mice received the diets for 180 days. Body weight and serum lipid levels were measured. Autophagic flux characteristics, such as accumulation of lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…In previous studies of young, female rats [ 37 , 43 ], all GSPE treatments ameliorated dyslipidaemia and the insulin-resistant state of obese rats. Other studies have also shown that GSPE protects against disorders in mice induced by a high-fat diet [ 44 ]. Contrary to our results, a dietary dose of GSPE (25 mg/kg BW) managed to reduce the plasma levels of triglycerides, glucose, and insulin in cafeteria-diet-fed male rats [ 45 ], while puerarin [ 46 ], resveratrol [ 47 ], and procyanidin B2 [ 17 ] ameliorated hyperglycaemia and hyperinsulinemia caused by an obesogenic diet.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of young, female rats [ 37 , 43 ], all GSPE treatments ameliorated dyslipidaemia and the insulin-resistant state of obese rats. Other studies have also shown that GSPE protects against disorders in mice induced by a high-fat diet [ 44 ]. Contrary to our results, a dietary dose of GSPE (25 mg/kg BW) managed to reduce the plasma levels of triglycerides, glucose, and insulin in cafeteria-diet-fed male rats [ 45 ], while puerarin [ 46 ], resveratrol [ 47 ], and procyanidin B2 [ 17 ] ameliorated hyperglycaemia and hyperinsulinemia caused by an obesogenic diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that grape seed proanthocyanidin extract (GSPE) alleviates oxidative damage in mouse testis and liver by activating Nrf2 signaling [46, 47]. Another study demonstrated that GSPE can reduce high-fat-diet- (HFD-) induced dyslipidemia in mice by attenuating the HFD-induced upregulation of miR-96 expression [48]. We previously found that GSPB2 alleviates oxidative stress-induced GC apoptosis by evoking an autophagic response [26].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of miR-96 by dietary saturated fatty acids impairs insulin signaling and exacerbates hepatic insulin resistance through the suppression of INSR and IRS-1 [276]. Grape seed proanthocyanidins extracts significantly decreases HFDinduced miR-96 upregulation in mice, and reduces the expressions of miR-96 downstream molecules, FOXO1, p-mTOR, mTOR, and LC3A/B [277].…”
Section: Mir-96mentioning
confidence: 99%